Fast & fresh cooking emagazine (Fast & Fresh Cooking.)
Serving up hearty family favorites doesn't mean spending a lot of time in the kitchen or paying for expensive hard-to-find ingredients. Let this handy collection of mouthwatering mainstays show you how! Best of all, every recipe serves up a complete listing of nutrition facts and diabetic exchanges when applicable.